Effect of Planting Systems on the Physicochemical Properties and Bioactivities of Strawberry Polysaccharides - Qiuqiu Zhang; Renshuai Huang; Guangjing Chen; Fen Guo; Yan Hu (Foods)
Suitable planting systems are critical for the physicochemical and bioactivities of strawberry (Fragaria × ananassa Duch.) polysaccharides (SPs). In this study, SPs were prepared through hot water extraction, and the differences in physicochemical characteristics and bioactivities between SPs derived from elevated matrix soilless planting strawberries (EP-SP) and those from and conventional soil planting strawberries (GP-SP) were investigated. A higher extraction yield was observed for EP-SP (5.88%) than for GP-SP (4.67%), and slightly higher values were measured for the average molecular weight (632.10 kDa vs. 611.88 kDa) and total sugar content (39.38% vs. 34.92%) in EP-SP. In contrast, a higher protein content (2.12% vs. 1.65%) and a more ordered molecular arrangement were exhibited by GP-SP. Monosaccharide composition analysis revealed that EP-SP contained higher levels of rhamnose (12.33%) and glucose (49.29%), whereas GP-SP was richer in galactose (11.06%) and galacturonic acid (19.12%). Thermal analysis indicated only minor differences in decomposition temperatures (approximately 225–226 °C) and thermal stability between the samples. However, GP-SP showed a higher enthalpy change (ΔHg = 18.74 J/g) compared to EP-SP (13.93 J/g). Biological activity assays revealed that GP-SP generally exerted stronger non-enzymatic glycation inhibition at both early and final stages (IC50: 7.47 mg/mL vs. 7.82 mg/mL and 11.18 mg/mL vs. 11.87 mg/mL, respectively), whereas EP-SP was more effective against intermediate α-dicarbonyl compounds (maximum inhibition of 75.32%). Additionally, GP-SP exerted superior α-glucosidase inhibition (IC50 = 2.4583 mg/mL), in line with kinetic and fluorescence quenching analyses showing a higher enzyme–substrate complex binding affinity (Kis = 1.6682 mg/mL; Ka = 5.1352 × 105 M−1). Rheological measurements demonstrated that EP-SP solutions exhibited a pronounced increase in apparent viscosity at higher concentrations (reaching 3477.30 mPa·s at 0.1 s−1 and 70 mg/mL) and a stronger shear-thinning behavior, while GP-SP showed a comparatively lower viscosity and lower network order. These findings suggest that different planting systems significantly affect both the molecular structures and functionalities of SPs, with GP-SP demonstrating enhanced hypoglycemic and anti-glycation properties. It is therefore recommended that suitable planting systems be selected to optimize the functionality of plant-derived polysaccharides for potential applications in the food and pharmaceutical industries.